2021
DOI: 10.1175/jcli-d-20-0498.1
|View full text |Cite
|
Sign up to set email alerts
|

Extratropical Southern Hemisphere Synchronous Pressure Variability in the Early Twentieth Century

Abstract: Because continuous meteorological observations across Antarctica did not start until the middle of the twentieth century, little is known about the full spatial pattern of pressure variability across the extratropical Southern Hemisphere (SH) in the early twentieth century, defined here as the period from 1905 to 1956. To fill this gap, this study analyzes pressure observations across the SH in conjunction with seasonal pressure reconstructions across Antarctica, which are based on observed station-to-station … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 65 publications
1
22
0
Order By: Relevance
“…although not statistically significant prior to 1979. In contrast, but consistent with the instrument-based sea-ice reconstructions of Fogt et al (2022), the pressure trends in the merged pressure dataset from Fogt and connolly (2021) show a reversal in pressure trends across Antarctica before and after 1979. Since a large portion of the Antarctic sea-ice extent in this region is driven by the atmospheric circulation, Figure 2b demonstrates that changes in the atmospheric circulation give rise to the differences between the Fogt et al (2022) reconstructions and those derived from paleoclimatological data.…”
Section: The Role Of Atmospheric Circulationsupporting
confidence: 85%
See 1 more Smart Citation
“…although not statistically significant prior to 1979. In contrast, but consistent with the instrument-based sea-ice reconstructions of Fogt et al (2022), the pressure trends in the merged pressure dataset from Fogt and connolly (2021) show a reversal in pressure trends across Antarctica before and after 1979. Since a large portion of the Antarctic sea-ice extent in this region is driven by the atmospheric circulation, Figure 2b demonstrates that changes in the atmospheric circulation give rise to the differences between the Fogt et al (2022) reconstructions and those derived from paleoclimatological data.…”
Section: The Role Of Atmospheric Circulationsupporting
confidence: 85%
“…Additionally, Fogt and connolly (2021) provide another pressure dataset, which employs a seasonal, spatially complete reconstruction poleward of 60°S (Fogt et al 2019) and the National Oceanic and Atmospheric Administration 20th-century reanalysis (Slivinski et al 2019) equatorward of 60°S. Importantly, the Fogt and connolly (2021) merged pressure dataset avoids large artificial trends in other datasets over Antarctica prior to 1957 and, therefore, likely provides a more robust estimate of 20thcentury pressure trends (Fogt and connolly 2021). Annual sea-level pressure trends from the two datasets are displayed in Figure 2b.…”
Section: The Role Of Atmospheric Circulationmentioning
confidence: 99%
“…Several hypotheses, related to a possible role of wind changes, modification of the deep convection in the Southern Ocean, the stratospheric ozone depletion or the teleconnections with the tropics, have been proposed for changes in sea-ice extent over the 20th century but no convincing explanation is currently available (Goosse et al, 2009;Fan et al, 2014;L. Zhang et al, 2019;Fogt & Connolly, 2021;Fogt et al, 2022;Schneider & Deser, 2018;Landrum et al, 2017). Over longer timescales, sea ice reconstructions from marine sediment cores suggest the influence of the SAM and ENSO is maintained over the past millennium (Crosta et al, 2021).…”
mentioning
confidence: 99%
“…Reconstructions of the Southern Annular Mode (SAM) (e.g., Abram et al, 2014) indicate neutral values. The most comprehensive analysis was performed by Connolly (2020) and Fogt and Connolly (2021). They presented a new reconstruction of pressure back to 1905 and found that the SAM signal also dominated in the early 20 th century, however, without addressing specifically this period.…”
mentioning
confidence: 99%
“…Based on the assessment by Fogt and Connolly (2021), 20CRv3 is a good starting point for studying this period. However, although it is widely and successfully used, very little pressure data was ingested into 20CRv3 during these years.…”
mentioning
confidence: 99%